Even small trade costs restore efficiency in tax competition - Johannes Becker; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2010)
We introduce transport cost of trade in products into the classical Zodrow and Mieszkowski (1986) model of capital tax competition. It turns out that even small levels of transport cost lead to a complete breakdown of the seminal result, the underprovision of public goods. Instead, there is a symmetric equilibrium with efficient public goods provision in all jurisdictions.
Keywords: H25; F23; 330; tax competition; public goods provision; trade; Kapitalertragsteuer; Steuerwettbewerb; Öffentliches Gut; Versorgung; Gleichgewichtstheorie; Transportkosten; Theorie